FEMS DENIM'S DIGITAL MARKETING STRATEGY TO GENERATE LEADS - Melisa
FEMS Denim is a startup company that focuses on customized fashion that wants to help customers get clothes that perfectly fit them. But no leads have been generated since launching. The issue can be seen from the low FEMS Instagram engagement, also zero sales. However, in the digital age, lead generation is now an essential component of any good marketing strategy since it allows businesses to reach a broader audience and generate more quality leads. Businesses may attract and convert new customers more effectively if they understand the notion of lead generation and how it works, resulting in increased growth and success. To address this issue, digital marketing may be used as a lead generation strategy by the company. The purpose of this research is to help the customized denim companies to generate leads using digital marketing strategies. Additionally, this research used a deductive methodology. The researcher used a framework theory by Ryan Deiss and Russ Hennebery, then analyzed it according to the company's internal and external conditions. The findings reveal that the best digital marketing strategy to generate leads is content marketing with specifically top of funnel marketing types as the first stage of the marketing funnel, the strategy chosen is based on the most likely to be implemented first according to the situation of the company and target customers. Thus, this research will result in a digital marketing strategy for customizable denim companies to generate leads.